Initial Acoustoelastic Measurements in Olivine: Investigating the Effect of Stress on P‐ and S‐Wave Velocities. Issue 11 (28th October 2021) - Traylor, T. K.; Burnley, P. C.; Whitaker, M. L.
Abstract: It is well known that elasticity is a key physical property in the determination of the structure and composition of the Earth and provides critical information for the interpretation of seismic data. This study investigates the stress‐induced variation in elastic wave velocities, known as the acoustoelastic effect, in San Carlos olivine. A recently developed experimental ultrasonic acoustic system, the Directly Integrated Acoustic System Combined with Pressure Experiments (DIASCoPE), was used with the D‐DIA multi‐anvil apparatus to transmit ultrasonic sound waves and collect the reflections. We use the DIASCoPE to obtain longitudinal ( P ) and shear ( S ) elastic wave velocities from San Carlos olivine at pressures ranging from 3.2–10.5 GPa and temperatures from 450–950°C which we compare to the stress state in the D‐DIA derived from synchrotron X‐ray diffraction. We use elastic‐plastic self‐consistent (EPSC) numerical modeling to forward model X‐ray diffraction data collected in D‐DIA experiments to obtain the macroscopic stress on our sample. We can observe the relationship between the relative elastic wave velocity change (Δ V / V ) and macroscopic stress to determine the acoustoelastic constants, and interpret our observations using the linearized first‐order equation based on the model proposed by Hughes and Kelly (1953), https://doi.org/10.1103/physrev.92.1145 . This work supports the presence of the acoustoelastic effect in San Carlos olivine, which can be measured as a function of pressure and temperature. This study will aid in our understanding of the acoustoelastic effect and provide a new experimental technique to measure the stress state in elastically deformed geologic materials at high pressure conditions. Plain Language Summary: Knowledge of the elastic properties of minerals is critical for understanding the structure and composition of Earth's interior and interpreting seismic data. This study investigates the effect of the stress state on P ‐ and S ‐waves velocities; known as the acoustoelastic effect. To our knowledge, the acoustoelasticity of geologic materials at conditions relevant to Earth's interior has not been evaluated. This study focuses on olivine, a mineral that comprises a large portion of the lithospheric mantle. We use a D‐DIA deformation apparatus to deform samples at high pressure and temperature while monitoring lattice parameters with synchrotron X‐ray diffraction and the sample length with X‐radiography. Simultaneously, we use ultrasonic interferometry to measure P ‐ and S ‐wave travel times. We use these data to determine P ‐ and S ‐wave velocities and the acoustoelastic effect as a function of pressure and temperature. We show that there is a measurable acoustoelastic effect in olivine that is nearly insensitive to changes in temperature and shows a minor pressure dependence. The effect is large enough that it may need to be considered in seismic data interpretation in regions where high stresses are present. Acoustoelastic properties may also be useful for directly measuring stress in lab‐based experiments. Key Points: We have experimentally measured the acoustoelastic effect in olivine at high pressure and temperature P ‐waves propagating along the axis of compression have a greater acoustoelastic sensitivity than S ‐waves Changes in the acoustoelastic constants as a function of pressure and temperature parallel those of the bulk and shear modulus